Changing views of cerebral palsy over 35 years: the experience of a center - Tosun, Ayşe; Gökben, Sarenur; Serdaroğlu, Gül; Polat, Muzaffer; Tekgül, Hasan (The Turkish Journal of Pediatrics, 2013)
In this study, it was aimed to evaluate the demographic and clinical characteristics of cerebral palsy (CP) cases over a 35-year period. Findings of 442 patients with CP followed from 1995 to 2006 (Group 2) were compared with 208 patients with CP followed between 1972 and 1994 (Group 1) in the same pediatric neurology division. Ratios of both prematurity (38% vs. 17.7%) and very low birth weight (VLBW) infants (13.8% vs. 1.5%) significantly increased in Group 2. There was also a four-fold increase in cesarean delivery in Group 2 (42.3% vs. 9.6%). A significant increase in the rate of early diagnosis during the first year was also found in this group (56.9% vs. 39.4%). The rate of spastic diparesis cases has significantly increased (33.7% vs. 7.7%), while the rate of spastic tetraparesis cases has significantly decreased (63.5% vs. 37.3%). It was seen that preventable risk factors continue today.